LAPORAN KEUANGAN BAZNASDI ERA DIGITAL 4.0: TINJAUAN ATAS PSAK 109 - Anis Choirun Nisa; Hanifah Indarwati; Siti Muthi’ah; Saiful Anwar (STAI Syubbanul Wathon Magelang, 2021)
This study aims to study BAZNAS 'financial statements with PSAK 109 and analyze the factors that affect the quality of BASNAZ financial reports in the digital era. This study used a qualitative descriptive approach, the Zaltman's Metaphor Elicitation Technique (ZMAT) method. The research location is in the National Zakat Agency (BAZNAS) Salatiga City. Information techniques through in-depth interviews and literature study. The data used are the financial statements of BAZNAS City of Salatiga for the fiscal year 2019. The results of the study, after the data were collected and compared with PSAK 109, it can be seen that BAZNAS Kota Salatiga 2019 has prepared financial reports according to the format contained in PSAK 109 single entry. However, there are several financial reports that claim to be incomplete according to the format in PSAK 109, among others, there is no non-halal data in their financial statements which only constitute assets, liabilities, and balance funds. Statements of cash flow and changes in BAZNAS funds in Salatiga City are in accordance with the format of PSAK 109. Inadequate human resources are a factor that causes inconsistencies between the format of the financial statements and the format of PSAK 109. In addition there are several other factors that can affect the quality of financial reports such as the accounting system which is also used in the use of technology applied at the Police. The contribution of this research is to provide an explanation of the proper presentation of financial statements and to explain the importance and benefits of digitizing the Salatiga BAZNAS financial statements.